INFLUENCE OF DIGITALIZATION ON INTERACTIONS BETWEEN PHARMACEUTICAL COMPANIES AND HEALTHCARE PROFESSIONALS IN MOROCCO - AGOULMAM , Ibtihal; CHAKOR , Abdellatif (Revue Internationale des Sciences de Gestion, 2024)
In healthcare, digitalization has become omnipresent, precipitating substantial changes across various procedures and dimensions of the sector. Healthcare practitioners are now under pressure to integrate digital technologies into their daily routines to trim costs, streamline specific tasks, and elevate overall care standards. Nevertheless, doubts persist regarding the efficacy of the tools ushered in by this technological shift, particularly regarding their impact on healthcare professionals’ contentment. With this backdrop, this article seeks to scrutinize this phenomenon by emphasizing the linkages between healthcare professionals’ satisfaction and the digitalization of the pharmaceutical domain. Through the administration of a comprehensive questionnaire to 133 healthcare practitioners in Rabat, featuring 25 items, we conduct statistical analyses to gauge reliability (Cronbach’s alpha), assess correlation between variables (Pearson coefficient), and empirically model interactions (linear regression). This study endeavors to illuminate the nuanced connection between digitalization and healthcare professionals’ satisfaction, imparting valuable insights into the ongoing discourse within this realm.